An Herbal Drug, Gongjin-dan, Ameliorates Acute Fatigue Caused by Short-Term Sleep-Deprivation: A Randomized, Double-Blinded, Placebo-Controlled, Crossover Clinical Trial - Son, Mi Ju; Im, Hwi-Jin; Ku, Boncho; Lee, Jun-Hwan; Jung, So Young; Kim, Young-Eun; Lee, Sung Bae; Kim, Jun Young; Son, Chang-Gue (Frontiers in Pharmacology, 2018)
Introduction: Gongjin-dan (GJD) is an herbal drug commonly used in Korea and China to combat fatigue, but there are only few clinical studies on its effectiveness and experimental studies on its mechanism of action, and no randomized controlled trial of GJD on the efficacy and mechanism of action has been reported. Here, we performed an exploratory study to evaluate both questions regarding GJD use in humans. Methods: A randomized, double-blinded, placebo-controlled, crossover clinical trial was conducted in the Republic of Korea. Healthy male participants were recruited and randomly allocated to groups receiving GJD-placebo or placebo-GJD in sequence. Fatigue was artificially induced by sleep deprivation for 2 nights. The primary outcome was a change in serum cortisol level; levels of biomarkers for stress hormones as well as oxidative stress and immunologic factors were also assessed, and questionnaires on fatigue and sleep quality were conducted. Results: Twelve and 11 participants were assigned to the GJD-placebo and placebo-GJD groups, respectively. Of all 23 participants, depending on crossover design, we analyzed a total of 20 participants for GJD, and 21 for placebo. An increase in serum cortisol appeared to be attenuated by GJD administration (p=0.25), but the effect was not statistically significant; a similar pattern was observed in salivary cortisol levels (p=0.14). Overall, GJD showed a tendency to reduce fatigue according to the Brief Fatigue Inventory (BFI, p=0.07) and the Fatigue Severity Scale (FSS, p=0.13) questionnaires. BFI and FSS scores in the first stage (before the crossover), however, were significantly improved (BFI, p=0.02; FSS, p=0.05) after GJD treatment (relative to placebo). GJD also seemed to improve sleep quality as assessed by the Leeds Sleep Evaluation Questionnaire (p=0.06), with a significant improvement specifically in the condition “Getting To Sleep” (p=0.02). Five participants experienced minor adverse events, but no adverse events were specific to the GJD administration period. Conclusions: This trial produced the first clinical evidence that GJD might have anti-fatigue properties, especially under sleep deprivation; however, the investigation of cortisol-mediated mechanisms requires further larger-scale studies in the future. Trial registration: World Health Organization International Clinical Trials Registry Platform KCT0001681 (http://apps.who.int/trialsearch/Trial2.aspx?TrialID=KCT0001681).